Motivasi Guru SD dalam Pelatihan Pembuatan Buku Saku Edukasi Lingkungan Berkelanjutan di Indragiri Hulu - Alpusari, Mahmud; Mustafa, M. Nur; Mulyani, Eva Astuti; Fendrik, Muhammad; Anggriani, Mitha Dwi; Guslinda; Barokah, Rifqa Gusmida Syahrun (BALE LITERASI, 2025)
The training on creating sustainable environmental education pocketbooks in Indragiri Hulu was motivated by the urgent need to raise environmental awareness and responsibility from an early age. The declining concern for environmental issues among the younger generation is a major concern, as many elementary school students are not yet accustomed to implementing environmentally friendly behaviors in their daily lives. The goal of this training was to improve teachers' skills and motivation in writing pocketbooks that incorporate sustainable environmental education values and enrich students' learning experiences. The training methods included material development, theories on environmental education and pocketbook production techniques, hands-on practice, and evaluation of the process and resulting product. The training results demonstrated an increase in teachers' motivation and skills in producing applicable and contextual environmental education pocketbooks. These pocketbooks are expected to be an effective learning medium for instilling environmental values in students and contributing to environmental conservation efforts. The success of this training has the potential to serve as a model for teacher competency development and environmental education programs in other elementary schools.